The "baguazo": how to inform - Arias Quincot, César (2010)
This pieces is about the tragic events occurred in Bagua due to thc clash the economic opening and globalization process against the conscrvative ideas that still prevail in a country like Peru, with a scarce and badly distributcd wealth. What triggered the Amazonian drama was the recently passed legislative decree to execute the FTA wirh USA. As soon as the communiry leaders from Bagua learned about, they demanded the revocatían of the USA-Peru FTA decree because thcy thought they would be dispossessed of their lands. Negotiations  only started aftcr conflict exploded, before that there was no dialog at all. This situation establishes that there are differences berween the actual facts and how these are presented in the media. In this case, the political and ideological approaches prevailed . For some  newspapers the native people were "Barbarians" or "savages" and suggested their repression as measure. Others, for a change, rejected repressive violence and the information disseminated showed more a balanced approach, whilst other foreign media took sides with the Amazonian people.